Total biomass and essential oil composition of Ocimum gratissimum L. in response to broiler litter and phosphorus - S.M. PESSOA; N.A. HEREDIA ZÁRATE; M.C. VIEIRA; C. A. L. CARDOSO; N.R. POPPI; A.S.N. FORMAGIO; L.R. SILVA (Universidade Estadual Paulista, 2015)
The aim of this experiment was to evaluate the biomass yield and chemical composition of the essential oil of clove basil in response to doses of broiler litter (0, 5, 10, 15 and 20 t ha-1) added in presence of triple superphosphate (200 kg ha-1) or without it. Before the first harvest, the height of the plants increased significantly (34.42 cm) when 15 tonnes ha-1 broiler litter were added to the soil. However, after resprouting, the plant heights ranged only as a function of the vegetative cycle, with maximum height (76.0 cm) observed at 60 days. Phosphate fertilization also significantly influenced the leaf area (1.771 cm2 plant-1) during the first harvest. The fresh weight of leaves increased linearly in response to the addition of broiler litter (20 ton ha-1) with maximum yields of 1,709 and 7,140 kg ha-1 during the first harvest and regrowth, respectively. On average, the oil content of the leaves was 0.7%, with maximum performance (3.8 L ha-1) when 20 tonnes ha-1 of broiler litter were added on the soil. Eugenol was found to be the major compound of the essential oil (71.65%).